Impact of Social Media on the Cultural Identity of the Young Generation in the Society 5.0 Era - Randi Ardiansyah; Muhammad Syamhuri (Gema Cendekia Institute, 2025)
The development of information and communication technology has brought very significant changes to the social life of modern society, especially among the younger generation. One of the tangible manifestations of this development is the presence of social media which is now an integral part of daily activities. Social media not only functions as a means of communication, but also as a space for self-expression, opinion formation, and arena for social and cultural identity construction. In the context of Indonesia's young generation, social media has a great influence in shaping their mindsets, behaviors, and ways of understanding and representing cultural identities in the midst of an increasingly strong flow of digital globalization. This study aims to describe the influence of social media on the construction of cultural identity of the young generation of Indonesia. The approach used is qualitative with a descriptive method, through in-depth interview techniques, observation, and literature study. The results of the study show that social media has an ambivalent role. On the one hand, social media can strengthen awareness of local culture through the dissemination of creative content with nuances of local wisdom. But on the other hand, social media also encourages a shift in values, lifestyles, and cultural symbols due to strong global cultural penetration. These findings confirm that digital literacy and culture-based character education are very important to equip the younger generation to be able to adapt critically without losing their identity and national values in the midst of the rapid flow of global modernization.